2007
DOI: 10.1002/prca.200700315
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic strategies in multiple sclerosis and its animal models

Abstract: The early and precise diagnosis, the prognosis, and the clinical management of multiple sclerosis, remain a considerable challenge. In recent years, the development of novel and powerful proteomic techniques prompted the use of these approaches for the search of unique biomarkers in the cerebrospinal fluid of multiple sclerosis patients. A few studies have also utilized proteomics to delineate the profile of differentially expressed proteins in animal models of the human disease in order to gain global insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 130 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…Therefore, a quantitative ‘top-down’ proteomic approach was carried out to resolve protein species from whole brains of the CPZ-fed(±PT) mice. To date, proteome analyses of MS have mainly assessed tissue from late-stage post mortem brain samples and cerebrospinal fluid [89,96] or EAE animals [88,93,100,105]; these analyses provide useful insight into the ‘final readout’ of the disease or its autoimmune aspects [131,132,133] but not necessarily insight into the processes involved in disease aetiology and progression, including the role of oligodendrocytosis [1,49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a quantitative ‘top-down’ proteomic approach was carried out to resolve protein species from whole brains of the CPZ-fed(±PT) mice. To date, proteome analyses of MS have mainly assessed tissue from late-stage post mortem brain samples and cerebrospinal fluid [89,96] or EAE animals [88,93,100,105]; these analyses provide useful insight into the ‘final readout’ of the disease or its autoimmune aspects [131,132,133] but not necessarily insight into the processes involved in disease aetiology and progression, including the role of oligodendrocytosis [1,49].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, due to its obvious limitations transcriptomics should be employed only with a clear and specific question in mind and carefully in view of the regulatory settings and potential pitfalls of the technique (Casciano and Woodcock, 2006;Fathallah-Shaykh, 2005). The same is true for the proteome approach (reviewed in Elkabes and Li, 2007;Linker et al, 2009a). In EAE, it has served to generate differential protein Table 2 Susceptibility genes of MS.…”
Section: Gene Expression Studies By Microarray Analysismentioning
confidence: 99%
“…Among the wide range of proteins that have been found to be exclusively present in the CSF of MS patients [125, 189, 191194], only some of them are expressed on neurons (contactin-1, neurofascin, neurotrimin, and chromogranins/secretogranins) [193195]. It was recently shown that contactin-2 was recognised by both autoantibodies and Th1/Th17 T-cells in MS patients [36, 37] and neurofascin-specific autoantibodies were identified in MS patients [196].…”
Section: Biomarkers Of Neuroaxonal Damage In Multiple Sclerosismentioning
confidence: 99%
“…Recently, a rapid development of proteomic approaches refocused biomarker research interest to the use of novel methods in the discovery of potential MS-specific biomarkers in biological fluids and especially in the CSF [ 189 , 190 ]. Among the wide range of proteins that have been found to be exclusively present in the CSF of MS patients [ 125 , 189 , 191 194 ], only some of them are expressed on neurons (contactin-1, neurofascin, neurotrimin, and chromogranins/secretogranins) [ 193 195 ]. It was recently shown that contactin-2 was recognised by both autoantibodies and Th1/Th17 T-cells in MS patients [ 36 , 37 ] and neurofascin-specific autoantibodies were identified in MS patients [ 196 ].…”
Section: Biomarkers Of Neuroaxonal Damage In Multiple Sclerosismentioning
confidence: 99%